If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -1(-1 + 8i) + -1(-7 + -1i) = 0 6 + (-1 * -1 + 8i * -1) + -1(-7 + -1i) = 0 6 + (1 + -8i) + -1(-7 + -1i) = 0 6 + 1 + -8i + (-7 * -1 + -1i * -1) = 0 6 + 1 + -8i + (7 + 1i) = 0 Reorder the terms: 6 + 1 + 7 + -8i + 1i = 0 Combine like terms: 6 + 1 = 7 7 + 7 + -8i + 1i = 0 Combine like terms: 7 + 7 = 14 14 + -8i + 1i = 0 Combine like terms: -8i + 1i = -7i 14 + -7i = 0 Solving 14 + -7i = 0 Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + -7i = 0 + -14 Combine like terms: 14 + -14 = 0 0 + -7i = 0 + -14 -7i = 0 + -14 Combine like terms: 0 + -14 = -14 -7i = -14 Divide each side by '-7'. i = 2 Simplifying i = 2
| (10x-5y)=1 | | 2-6(r-6)=2+6(r-2) | | 4a-7=-59 | | 85+5x+10=180 | | 14=3v+5(v-2) | | 4a-7=59 | | b=1.5mv | | 9-8q+4q= | | 2q+1q= | | 75=6x+5x+9 | | 52+2x-6=180 | | -5-2n=21 | | 3(5n)+14+6n=21 | | -2(3x+6)=12 | | x(x+5)=210 | | 2X^2+-8X=0 | | 5(r-2)=-16+6r | | (-2x+4)-(-6x-7)= | | 3x-45=2y | | -6(2x-1)=0 | | x^2-15=-7x+2 | | 23-5n=-7(n-3)-4 | | 0.1x+0.2y=-0.2 | | Log^4*16=2 | | 7x-(5x+4)=9x-25 | | 25=2u+3u | | 2(x+4)4=0 | | 7.4x-13.4=31 | | 8u-u=21 | | 128-4y+2y=100 | | (c-3)(2c)=2c(c-3)-c^2+4 | | 16x-14=-110 |